2007
DOI: 10.1186/1471-2199-8-93
|View full text |Cite
|
Sign up to set email alerts
|

Detection limits of several commercial reverse transcriptase enzymes: impact on the low- and high-abundance transcript levels assessed by quantitative RT-PCR

Abstract: Background: In functional genomics, transcript measurement is of fundamental importance. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) assays are the most popular technology and depend on the initial molecular step, the reverse transcription (RT). This study provides a complex overview of the influence of elements such as RT systems, amount of background RNA, and transcript abundance on the efficiency of qRT-PCR. Using qRT-PCR, we compared the efficiency of some commonly used RT system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 31 publications
5
82
4
Order By: Relevance
“…At this regards, in this study an external in vitro synthesized cRNA standard is generated in order to obtain a calibration standard curve, thereby offering some advantages as control and standardization of RNA extraction and reverse transcription. The sensitivity of our assay was found to be of 100 copy/reaction with a linearity range from 10 (9). Overall, the unique condicio sine qua non for cRNA standard synthesis is represented by the presence of a RNA polymerase promoter-binding site into the vector containing the amplicon of interest (many commercial products, comprising those used in our protocol, are characterized by the presence of T7-RNA polymerase promoter) and the choice of the in vitro transcription kit depends on it (5).…”
Section: Discussionmentioning
confidence: 99%
“…At this regards, in this study an external in vitro synthesized cRNA standard is generated in order to obtain a calibration standard curve, thereby offering some advantages as control and standardization of RNA extraction and reverse transcription. The sensitivity of our assay was found to be of 100 copy/reaction with a linearity range from 10 (9). Overall, the unique condicio sine qua non for cRNA standard synthesis is represented by the presence of a RNA polymerase promoter-binding site into the vector containing the amplicon of interest (many commercial products, comprising those used in our protocol, are characterized by the presence of T7-RNA polymerase promoter) and the choice of the in vitro transcription kit depends on it (5).…”
Section: Discussionmentioning
confidence: 99%
“…The formula takes into account the respective amplicon length generated during real-time PCR (Supplementary Table 3) as described (Lalancette et al 2008b). Only the absolute transcript copies were normalized using the exogenous EGFP transcripts as described (Levesque-Sergerie et al 2007), whereas the relative method readily includes a normalization using PPIA, an endogenous 'housekeeping' gene. All points of the standard curves and each query samples were carried out with triplicates and run in the ABI PRISM 7500 Sequence Detection System with software version 1.4 (Applied Biosystems).…”
Section: Qrt-pcr Data Analysismentioning
confidence: 99%
“…In order to normalize the difference in RT efficiencies across samples, each RT reactions was spiked EGFP mRNA. An equivalent of 1 pg/mg of spermatozoal RNA was added in pooled RNA and each RT reaction made with 1 mg included an equal amount of EGFP transcripts in each 20 ml reaction as described (Levesque-Sergerie et al 2007). …”
Section: Reverse Transcriptionmentioning
confidence: 99%
“…Increase of commercial master mix kits enabled diagnostic laboratories to implement real-time PCR. It has been demonstrated that the reverse transcription reaction mainly depends on the initial molecular step (the reverse transcription), choice of master mix reagents, quality of enzymes, concentration of reaction mix components, such as primers, probes and methodology used that can impact the sensitivity of results for real-time PCR assays (SERGERIE et al, 2007;BUZARD et al, Ciência Rural, v.46, n.9, set, 2016.…”
Section: Resultsmentioning
confidence: 99%